Click Pt(IV)-Carbohydrates Pro-Drugs for Treatment of Osteosarcoma - Moynihan, Eoin; Bassi, Giada; Ruffini, Andrea; Panseri, Silvia; Montesi, Monica; Velasco-Torrijos, Trinidad; Montagner, Diego (Frontiers in Chemistry, 2021)
The selectivity vs. cancer cells has always been a major challenge for chemotherapeutic agents and in particular for cisplatin, one of the most important anticancer drugs for the treatment of several types of tumors. One strategy to overtake this challenge is to modify the coordination sphere of the metallic center with specific vectors whose receptors are overexpressed in the tumoral cell membrane, such as monosaccharides. In this paper, we report the synthesis of four novel glyco-modified Pt(IV) pro-drugs, based on cisplatin scaffold, and their biological activity against osteosarcoma (OS), a malignant tumor affecting in particular adolescents and young adults. The sugar moiety and the Pt scaffold are linked exploiting the Copper Azide Alkyne Cycloaddition (CUAAC) reaction, which has become the flagship of click chemistry due to its versatility and mild conditions. Cytotoxicity and drug uptake on three different OS cell lines as well as CSCs (Cancer Stem Cell) are described.